Ultraductile waterborne epoxy-concrete composite repair material: Epoxy-fiber synergistic effect on flexural and tensile performance. (May 2022) - Pang, Bo; Jin, Zuquan; Zhang, Yunsheng; Xu, Lei; Li, Mengyuan; Wang, Chencui; Zhang, Yu; Yang, Yane; Zhao, Peng; Bi, Jinxu; Zhu, Weiwei; Shen, Yang; et al.
Abstract: With the extension of service time, infrastructure is in growing urgency for repair and reinforcement due to its deterioration in safety and durability over the years. Normal cement concrete has shortcomings, e.g., high brittleness and low flexural-tensile strength, that fail to meet the requirements of construction repair. In this paper, a novel waterborne epoxy-concrete composite repair material (WECM) was prepared by using self-synthesized water-based epoxy resin based on the molecular structure-activity relationship. The mechanisms of waterborne epoxy (WEP) and WEP-fiber synergy on the improvement of concrete performance were clarified. The results show that the defects of high brittleness and poor ductility of concrete are significantly improved by WEP and that the ductility of WECM is increased by 300%–600% compared with the control concrete. The fiber and WEP in the WECM exhibited a synergistic effect on the tensile strength, ductility, and crack resistance of concrete in which the fiber coating layer mixed with WEP and embedded cement particles (inlay) provided fiber protection as well as an interfacial bonding enhancement. The P/C of 0.2 is the turning point of the flexural and tensile strength of the WECM, which is related to the continuous phase formation of the WEP-interpenetrating polymer network (WEP-IPN).